(untitled) (Journal of Student Affairs in Africa, 2021)
Leadership and mental health came under the spotlight when more than 50 student leaders from all over the world met at Stellenbosch University (SU) from 23 to 26 June 2019 for the International Association of Student Affairs and Services (IASAS) Student Leader Global Summit. It was the first time that SU hosted this global summit for student leaders. IASAS is a nonprofit organisation that was founded in Belgium in 2013. It is a worldwide association of university professionals working in the area of student affairsand services. IASAS has more than 1 400 individual, institutional and association members representing over 90 countries on five continents.The fourth IASAS Student Leader Global Summit (SLGS) welcomed 45 students from 14 countries across the world. The SLGS provides a global platform for improving multi- and intercultural communication and understanding amongst students. The goal of the summits is to bring student leaders from different parts of the world together to discuss student governance, leadership, social justice and other topics of shared interest.